2012
DOI: 10.1039/c2dt30754e
|View full text |Cite
|
Sign up to set email alerts
|

Terphenyl-phenanthroline conjugate as a Zn2+ sensor: H2PO4− induced tuning of emission wavelength

Abstract: A new terphenyl-based macrocycle 5 incorporating phenanthroline as a fluorophore has been designed, synthesized and examined for its recognition ability toward various cations (Pb(2+), Hg(2+), Ba(2+), Cd(2+), Ag(+), Zn(2+), Cu(2+), Ni(2+), Co(2+), K(+), Mg(2+), Na(+) and Li(+)) by UV-vis, fluorescence and NMR spectroscopy. The receptor 5 showed highly selective 'Off-On' fluorescence signaling behavior for Zn(2+) ions in THF. Interestingly, the addition of H(2)PO(4)(-) ions to the [5-Zn] complex regulates the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Herein we report, a diformyl thioether based fluorescent chemosensor, H 2 ‐SAP , prepared by simple Schiff base condensation procedure ( Scheme S1 ) which displays selective fluorescence sensitivity towards Zn 2+ by chelation enhancement fluorescence effect (CHEF) process in presence of large number of ions and could identify Zn 2+ in nM level, much lower than so far reported results . The composition of the complex formed between Zn 2+ and H 2 ‐SAP has been supported by spectroscopic data (Mass, Job's plot) and single crystal X‐ray crystallography.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Herein we report, a diformyl thioether based fluorescent chemosensor, H 2 ‐SAP , prepared by simple Schiff base condensation procedure ( Scheme S1 ) which displays selective fluorescence sensitivity towards Zn 2+ by chelation enhancement fluorescence effect (CHEF) process in presence of large number of ions and could identify Zn 2+ in nM level, much lower than so far reported results . The composition of the complex formed between Zn 2+ and H 2 ‐SAP has been supported by spectroscopic data (Mass, Job's plot) and single crystal X‐ray crystallography.…”
Section: Introductionmentioning
confidence: 70%
“…Chemical sensing via fluorescence signal recognition has been first established during 1980s . Since then researchers are engaged to design various types of fluorogenic sensors to detect Zn 2+ in different environment including intracellular measurements, Fluorogenic motifs like naphthyl, Diformyl derivative, terpyridyl, quinoline,, imidazoylpyridyl,, bipyridyl,, pyrenyl derivatives, terphenyl‐based motif, pyrimidinyl attached Schiff‐base, pyrazolyl,, BINOL, rhodamine,, catechol appended Schiff base, coumarinyl Schiff base, thiazolyl derivative etc. have successfully been used.…”
Section: Introductionmentioning
confidence: 99%
“…showed that the binding of F − /CH 3 COO − ions to the Zn 2+ center of the terphenyl‐based macrocyclic complex ( 8 ) could trigger the release of Zn 2+ ion. A rather contrasting behavior was observed with H 2 PO 4 − , which formed a ternary complex with the metal ion (Zn 2+ ) through electron‐rich oxygen centers . Irrespective to their binding modes all of these aforementioned anions (H 2 PO 4 − , F − /CH 3 COO − ) quenched the emission intensity of the preformed Zn‐complex (no discrimination was possible).…”
Section: Single Molecular Probes For Simultaneous Detection Of Multipmentioning
confidence: 98%
“…À , which formed a ternary complex with the metal ion (Zn 2 + ) through electron-rich oxygen centers. [78] Irrespective to their binding modes all of these aforementioned anions (H 2 PO 4 À , F À / CH 3 COO À ) quenched the emission intensity of the preformed Zn-complex (no discrimination was possible). However, revival of the original emission by subsequent addition of Zn 2 + was possible only in case of F À /CH 3 COO À , not with H 2 PO 4 À .…”
Section: Displacement Vs Ternary Complexationmentioning
confidence: 99%
See 1 more Smart Citation